Assessment of morbidity and mortality associated with endoscopic ultrasound‐guided fine‐needle aspiration for pancreatic cystic lesions: A systematic review and meta‐analysis. Issue 6 (6th June 2017) - Zhu, Huiyun; Jiang, Fei; Zhu, Jianwei; Du, Yiqi; Jin, Zhendong; Li, Zhaoshen
Abstract : Background and Aim: With increased availability of imaging technology, detection of pancreatic cystic lesions (PCL) is on the rise. Endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) improves the diagnosis accuracy of PCL. Systematic evaluation of morbidity and mortality associated with EUS‐FNA for PCL has not been carried out. We conducted a systematic review and meta‐analysis of morbidity and mortality associated with EUS‐FNA. Methods: A literature search for relevant English‐language articles was conducted on PubMed and EMBASE databases. Main outcome measures for this analysis were adverse effects of diagnostic EUS‐FNA, and the associated morbidity and mortality, in patients with PCL. Results: Forty studies, with a combined subject population of 5124 patients with PCL, satisfied the inclusion criteria. Overall morbidity as a result of adverse events of EUS‐FNA was 2.66% (95% confidence interval [CI]: 1.84–3.62%), and the associated mortality was 0.19% (95% CI: 0.09–0.32%). Common post‐procedure adverse events included pancreatitis 0.92% (95% CI: 0.63–1.28%), hemorrhage 0.69% (95% CI: 0.42–1.02%), pain 0.49% (95% CI: 0.27–0.79%), infection 0.44% (95% CI: 0.27–0.66%), desaturation 0.23% (95% CI: 0.12–0.38%) and perforation 0.21% (95% CI: 0.11–0.36%). There was no peritoneal seeding in our study. Incidence of adverse events associated with prophylactic periprocedural antibiotic use was 2.77% (95% CI: 1.87–3.85%). Conclusions: EUS‐FNA is a safe procedure for diagnosis of PCL and is associated with a relatively low incidence of adverse events. Most adverse events were mild, self‐limiting, and did not require medical intervention.